Self and Illness: Changing Relationships in Response to Life in the Community Following Prolonged Institutionalisation - Newton, Liz (The Australian journal of anthropology, 2001)
Increasingly since the 1950s mentally ill people in the Western world have been removed from institutional care. In this paper I am concerned primarily with the response of psychiatric patients to living in a ‘normal’ community environment, in particular the extent to which they are able to assume new social roles and identities after long periods of institutional care. I conclude that despite persistent mental illness, deinstitutionalised patients have developed new roles and new identities, a new sense of independence, new coping abilities and a capacity to articulate future goals and desires. The findings are drawn from two and a half years fieldwork in an Australian capital city, where a group of long-stay psychiatric in-patients, who would not normally be considered for discharge, were given the opportunity to live in mainstream society. This accompanied the reduction of in-patient beds and the eventual closure of a large psychiatric hospital as it amalgamated with another hospital nearby.